Pengembangan Media Flipbook Interaktif Berbasis Kearifan Lokal untuk Meningkatkan Literasi Membaca Siswa Sekolah Dasar: Development of Interactive Flipbook Media Based on Local Wisdom to Improve Elementary School Students' Reading Literacy - Ike Heny Suprapti; Wahyu Sukartiningsih; M Bambang Edi Siswanto (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2026)
Reading literacy is a basic competency that elementary school students must have, but the reading literacy ability of Indonesian students is still relatively low. A similar condition was found in third-grade students of Sepaku Elementary School who experienced difficulties in understanding the content of reading, determining the main idea, and concluding. This study aims to develop an interactive flipbook media based on the local wisdom of the Indonesian Capital Region to improve the reading literacy of elementary school students. The study used the Research and Development method with the ADDIE model, which includes the stages of analysis, design, development, implementation, and evaluation. The research subjects consisted of 20 third-grade students. Data collection techniques used observation, interviews, questionnaires, documentation, and pretest and posttest tests. Data were analysed using the percentage of feasibility, practicality, and the N-Gain test. The results showed that the media obtained an average validity of 90.0% with a very feasible category, consisting of validation from material experts, 92.5%, media experts, 85.0%, and language experts, 92.5%. The level of practicality of the media reached 93.4%, with a very practical category. The effectiveness of the media showed an increase in students' average score from 70.95 in the pretest to 80.85 in the posttest, with an N-Gain value of 0.34, categorised as moderate. The novelty of the research lies in the integration of interactive digital media, Sepaku local wisdom content, and guided reading methods in one learning product. The interactive flipbook media based on local wisdom was declared feasible, practical, and effective in improving elementary school students' reading literacy.